VD_FINDINFO Arrêt / 2024 / 1016 vom 25. November 2024 - VD Tribunal cantonal (2024)
AC, APTITUDE AU PLACEMENT, ENCOURAGEMENT D'UNE ACTIVITÉ LUCRATIVE INDÉPENDANTE | 15 al. 1 LACI, 71a LACI, 71b LACI, 8 al. 1 let. f LACI